“Eu não estou aqui... Aliás, eu estou aqui!”: o processo de invisibilidade e visibilidade da Beata Maria de Araújo em Juazeiro do Norte - CE - Diniz, Priscila Ribeiro Jeronimo (2021)
The Juazeiro do Norte-CE story starts by the occurrence of a religious event with the Transubstantiation of a communion bread into blood by the Beatus Maria de Araújo, along with Father Cicero, the scene of the bleeding in the mouth of this woman repeated for years, the reason behind the story is the hiding over the years, and so prevailed, for decades. Little by little the scene reappears with the remembrance and speeches about Maria de Araújo, a cloistered woman, vilified and silenced in the XIX century, without a tomb, and out of the city history. Because of this invisibilization comes the problem of this research: whose objective is analyzing the process of invisibility and visibility of the Beatus Maria de Araújo in the social and religious story of Juazeiro do Norte. The methodological resources to follow the objective was qualitative approach, with exploratory and explanatory method, through the documental research in the inquiries I and II, and field research in the Juazeiro pilgrimages between 2017 and 2020, to funnel said question observations and interviews were made, wich appear in this thesis. Therefore, this paper has been divided in four chapters, the first displays the construction of the communion bread miracle scene and the protagonism of the Beats; The second observes the silencing and the invisibility wich builds aside Maria de Araújo, through Father Alexandrino and Bishop Dom Joaquim, that been said the romanticizing of the Brazilian catholic church the topic is visible, the fear of female Beatus, and the repression in Juazeiro so it doesn’t turn into a pilgrimage place, presenting the beatus in the representation of fear, in the night regimen of imaginary studies and heading her into silence of social and religious memory of Juazeiro do Norte. The third chapter is marked by a time passage, of almost ninety years in wich it can’t be talked about Maria de Araújo in the city. Therefore, the process of visibility starts to include the Beatus in academic subjects, in social and artistic movements; at last, the final chapter comes to show the crescent visibility through the Independent Moviment of Memorialist Pilgrims for the rehabilitation of Beatus Maria de Araújo, with actions and events, bringing the beatus to a new spot of image, in the regimen of twilight. In conclusion a speech existed and built a memory of silencing Maria, by the fear of its representation and today a movement of remembrance by rehabilitation of the Beatus, permeated by many speeches constructing a new image that slowly takes its shape.